The Awakening of Islamic Movement After the Islamic Revolution in Iran - Karimkhan, Ahmad (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2023)
Various studies have examined the Islamic Revolution in Iran, analyzing its nature, key features, societal effects, and future outlook. The Islamic revolution has significantly influenced societal behavioral and ethical standards, particularly within education, cultural practices, and religious observances. It has deeply impacted the collective identity and perspective of Iranian society. This study investigates how Islamic cultural principles shape moral conduct and social behavior across different societal domains. Findings suggest that the Islamic Revolution has instilled a distinct cultural ethos in Iran, marked by its emphasis on justice, social equity, resilience, unity, spirituality, and religious precepts. Recognizing the Islamic Revolution's impact on Iran's cultural and social landscape is essential for comprehending its ongoing challenges and future trajectory. Based on these findings, further exploration of the Islamic Revolution's role in shaping Iran's cultural and social identity, and its broader societal implications, is recommended.